Good laboratory practice: roles and responsibilities - Long, David (Henry Stewart Talks, 2012)
Responsibilities of Sponsors, Management, Study directors, Principal investigators, Archivists, Storage/Retention of records/materials, Quality assurance, Documenting roles and responsibilities, Organisation chart, Curriculum vitae, Job descriptions, Training & Archive records